Pengaruh Beban Kerja dan Perputaran Karyawan Terhadap Kinerja Karyawan - Yusuf Taufik; Farina Jessen Yap; Free Antonius Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
X is one of the distribution agents of PT. Y whose main focus is on the distribution of BBM (Fuel Oil). The phenomenon in the company is that employee performance decreases because the workload received by employees is too heavy and employee turnover is quite high.This research uses quantitative descriptive research. The total population in the study was 93 employees with the sampling technique using saturated samples so that there were 93 samples.Simultaneously there is a significant effect between workload and employee turnover variables on the performance of PT. X. While partially found the workload variable has no significant effect on the performance of employees of PT. X. Partially it was found that the employee turnover variable had no significant effect on the performance of the employees of PT. X.